Sustainable constructions: building materials, certifications and LCA (2011)
Current environmental conditions demand revaluating the professional practice of architecture, urbanism and building construction. To serve that purpose, the article presents various certifications granted throughout the world to help the professionals above mentioned to put up “green” structures; other specifications for building materials to be considered “sustainable”; and Life Cycle Assessment (LCA) techniques to analyze constructions’ cradle-to-grave behavior, for measuring building’s environmental impact as well as corroborating its sustainability.